Everyone on this train is a suspect : a novel [large type] - Stevenson, Benjamin (Harper Large Print, an imprint of HarperCollins Publishers, 2024)
"On a famous Australian train between Darwin and Adelaide for the Mystery Writers' Society one of the attendees is murdered for real"--